1998
DOI: 10.1139/t98-016
|View full text |Cite
|
Sign up to set email alerts
|

Laterally loaded piles in sand: slope effect on P-Y reaction curves

Abstract: An extensive program of centrifuge tests was undertaken to study the effect of slopes on P-Y curves in dry sand. The paper concerns the method developed in a previous series of centrifuge tests to experimentally determine P-Y curves. Bending-moment curves are fitted by local quintic spline functions through a crossed validation method and then differentiated twice. These experimental P-Y curves are validated by back analysis. The program of tests on piles near slopes is given. It includes studies of the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(28 citation statements)
references
References 1 publication
2
26
0
Order By: Relevance
“…It was found that the horizontal ultimate capacity of vertical pile decrease as the slope became steeper. Bouafia & Bouguerra (1995) and Mezazigh & Levacher (1998) performed centrifuge tests to study the responses of piles in/near a slope under lateral loads. The results showed that, for a pile at the crest of a 1 (V) : 2 (H) slope, the lateral capacity and the maximum bending moment are approximately 0.70 and 1.25 times those for the reference pile in Horizontal ground surface.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the horizontal ultimate capacity of vertical pile decrease as the slope became steeper. Bouafia & Bouguerra (1995) and Mezazigh & Levacher (1998) performed centrifuge tests to study the responses of piles in/near a slope under lateral loads. The results showed that, for a pile at the crest of a 1 (V) : 2 (H) slope, the lateral capacity and the maximum bending moment are approximately 0.70 and 1.25 times those for the reference pile in Horizontal ground surface.…”
Section: Introductionmentioning
confidence: 99%
“…The -method is based on the numerical solution of beam-on-elastic foundation, where the structural behavior of a drilled shaft is modeled as a beam and the soil-shaft interaction is represented by discrete, inelastic springs characterized by -curves [3,4]. However, two models cannot be extended to sloping ground since the spring constants for elastic or inelastic cases have not been clearly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The variation of passive resistance depending on ground slop is very significant for sloping ground. Recently, some developments towards the analysis of piles in sloping ground have been made either by experiments in laboratory [3,4] or by numerical analysis [5,6]. Results indicate that ground inclination significantly affects ultimate load of the -curves according to loading direction, angle of inclined pile and soil density, and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…However, some developments towards the analysis of piles in sloping ground have been made recently either by conducting experiments in laboratory (Mezazigh andLevacher 1998, Muthukkumaran et al 2004) or by performing numerical analysis, mainly based on available commercial software (Gabr andBorden 1990, Chae et al 2004). Several investigators have considered the equivalent problem of battered piles in horizontal ground.…”
Section: Introductionmentioning
confidence: 99%